Direct clinical applications of natural language processing in migraine: a literature review - Lima, Eduarda Maia; Lima, Rayndrick Kelryn Assis; Lima, Raynrich Kevin Assis; Santos, Isabela Cacau Sousa; Appio, Pedro Roa; Macêdo, Carolina Helen Soares de; Filho, Helvécio Neves Feitosa; Furtado, Nithyananda Araújo; Carate, Caio Kacem (Headache Medicine, 2023)
Full abstract in PDF.